Pain assessment and management in a neonatal intensive care unit: The perspective of the nursing team (Research, Society and Development, 2023)
This study aimed to identify the knowledge and practices of the nursing team regarding the assessment and management of pain in newborns admitted to the Neonatal Intensive Care Unit. This is an exploratory-descriptive research with a qualitative approach, whose final sample included 21 subjects. Data were collected through a semi-structured questionnaire from the google forms platform. With regard to the evaluation of the painful process, the evaluation scales used by the team include the NIPS and COMFORT-B. As for the management of neonatal pain, it was mentioned that analgesic therapies are used only in specific procedures after assessing the real need, such as in cases of phlebotomy, orotracheal intubation, chest drain and passage of Peripherally Inserted Central Catheter (PICC). With regard to non-pharmacological measures, the professionals mentioned the routine use of measures such as the kangaroo method/skin-to-skin contact, positioning, the cigar technique and non-nutritive sucking. The nursing team demonstrated that they considered the importance of controlling and treating this vital sign and its possible short- and long-term repercussions when neglected. It was evident that some professionals do not use and do not perceive a favorable impact on the use of scales, claiming that only the subjective evaluation of the team is sufficient.